ANALISIS STATISTIK PERTANDINGAN PADA POSISI BERMAIN CENTER CABOR BOLA BASKET TIM POMNAS JATIM PUTRA - Noval Dailami, Rahmad; Himawan, Agus; Putri Purwoto, Septyaningrum; Yuli Handayani , Heni (JURNAL ILMU KEOLAHRAGAAN, 2024)
The purpose of this research is to find out the results of the statistical analysis of matches in the center playing position for the POMNAS East Java Men's Basketball Team. In this research the author used a quantitative research method using a descriptive type. The population and sample in this study is the center playing position on the men's East Java Pomnas team who played in the "2023 South Kalimantan Pomnas" match. The technique used in collecting data in this research is using documents, the documents themselves are in the form of print outs of match statistics for "Pomnas Jatim Putra" who played in the "POMNAS KALSEL 2023" match. Based on the results of research on statistical analysis of matches in the playing position of the POMNAS East Java Men's Basketball Sport Center Center in the first, second and third matches, it can be concluded that the first center in the 1st to 4th quarter was successful at 24/44, while in the first, second and third matches The second center managed 8/40 in quarters 1, 2, 3 and 4.